Optimization Removal of COD and Nitrogen at Different Hydraulic Retention Times in Biocord-Integrated Fixed-Film Activated Sludge System: 10.32526/ennrj/20/202100254 - Thi Tuyet Nhi, Nguyen; Thi Thuy Van, Phan; Thi Thao, Nguyen; Thi Thanh Truc, Nguyen; Le Truong Khanh Hung, Tran; Thi Ngoc Tay, Do; Tan Nhut, Huynh; Trung Hiep, Nguyen (Environment and Natural Resources Journal, 2022)
Although conventional activated sludge has been demonstrated to be a feasible approach for extracting nitrogenous chemicals and organic pollutants from wastewater, it still has a number of drawbacks. In this research, a pilot-scale biocord-integrated fixed-film activated sludge (Biocord-IFAS) reactor fed with actual domestic wastewater was operated to examine the effect of varying hydraulic retention time (HRT) on the COD and nitrogen removal. The type of material employed in this study is fibrous polypropylene (biocord), which is a major difference. The contribution of the Biocord-IFAS to COD removal efficiency reached 94.2% at HRT of 8 h and gradually decreased to 82.9% when HRT was reduced to 4 h. During the investigation period, a slight decrease in nitrification was found at a shorter HRT. The NH4+-N removal efficiencies at HRTs of 10, 8, 6, and 4 h were 97.8%, 98.7%, 97.1%, and 96.3%, respectively. The average effluent nitrate concentration was 5.3 mg/L with HRTs from 10 to 6 h, but over 30 mg/L with an HRT of 4 h. The SEM analysis results show that microorganisms have formed on the biocord surface. The results of this research have demonstrated the potential application of IFAS reactors in bioremediation procedures employing biocord material with great processing efficiency.